Body mass index in adult patients with diet‐treated phenylketonuria. (3rd April 2013) - Robertson, L. V.; McStravick, N.; Ripley, S.; Weetch, E.; Donald, S.; Adam, S.; Micciche, A.; Boocock, S.; MacDonald, A.
Abstract: Background: There is an increasing number of adults with phenylketonuria (PKU) on a low phenylalanine diet. In the general population, an increasing body mass index (BMI) in the UK is a major problem with associated co‐morbidities. The present study aimed to identify whether patients with diet‐treated PKU have obesity rates comparable to those in the general population. Methods: Two hundred and thirty‐six PKU subjects (49% male, 51% female), aged >16 years, who were diagnosed by newborn screening and were receiving a low phenylalanine diet, were identified from seven metabolic centres in the UK. Retrospective data were collated on age, sex, BMI and mean phenylalanine concentration over the previous 12 months. Results: Mean (SD) phenylalanine concentration for all 236 subjects was 789 (311) μm ; mean (SD) BMI was 26 (5.4) kg m −2 [males 25 (4.3) kg m −2, females 27 (6.2) kg m −2 ]; mean (SD) age was 26 (7) years; and 55% had a BMI > 25 kg m −2 . The percentage of subjects with a BMI >25 kg m −2 and >30 kg m −2, as well as increasing obesity with age, was similar to the UK population. A correlation was observed between increasing BMI and a higher phenylalanine concentration ( r = 0.243, P = 0.001). Conclusions: The number of overweight and obese patients with diet‐treated PKU in the UK is a concern. This could lead to other obesity‐related complications increasing the complexity of diet and the cost of their care. There is a need to educate patients with respect to adopting a healthy, low phenylalanine diet and lifestyle to prevent further rises in BMI.